Regional Connectivity in Pakistan and Central Asian Republics <subtitle>Prospects and Challenges</subtitle> - Sarwat Rauf (China Quarterly of International Strategic Studies, 2021)
This article analyzes the emerging economic corridors and growing geographical connectivity in Pakistan and Central Asian Republics (CARs). It hypothesizes that economic corridors and infrastructure building in CARs and Pakistan are connecting inaccessible areas to prosperous regions. The idea of geographical connectivity through economic corridors is not new for landlocked Central Asia and least connected South Asia. In the past some efforts have been made to connect South Asia with Central Asia by great powers. However, such efforts had been overshadowed by tensions between key regional states and political hostilities within states. Since China is facilitating Pakistan and CARs in the building of new infrastructure to make remote areas accessible, several political and regional changes are taking place. Construction of new corridors presents diverse challenges for Pakistan and Central Asia. The article specifies a conceptual understanding of regional connectivity through economic corridors, and then underlines the set-up of new infrastructure. It also assesses the problems attached to the connectivity projects. Currently, connectivity projects under the Belt and Road Initiative have been modernizing the old trade routes in Central and South Asia, and new infrastructure is being built, granting opportunities of increased trade. Even though the announcement of regional connectivity projects by China in Pakistan and CARs has raised hopes as well as suspicions, CARs and Pakistan are visibly involved in the accomplishment of regional connectivity.